Torsional behaviour of axially discontinuous frame structure with c-shaped thin-walled sections for different lip sizes / Antonio Lapan Anak Rejap - Anak Rejap, Antonio Lapan (1998)
The main objective of this project is to study and observe the torsional behaviour of simple axially discontinuous frame structures. For this project, general purpose finite element computer package called "ANALYSIS SYSTEM" (ANSYS Release 5.0) was used to model and analyse the torsional behaviour of frame member having C-shaped thin walled sections of different lip sizes connected via different joint configurations under torsional load.